Public Knowledge of Law Number 14 of 2019 on Social Worker and the Implementation of Social Work in Indonesia - Risna Resnawaty; Alfrojems; Leny Jakaria; Dea Triantara Wibawa; Ahmad Zulfa Styabudi; Ena Rodiah (Indonesian Social Work Consortium (ISWC), 2022)
The ratification of Law Number 14 of 2019 on social worker provides a new chapter for social workers in Indonesia. The existence of this law certainly provides a large enough opportunity for social workers to be able to open up more opportunities in providing quality and equitable social services in all regions in Indonesia. however, what needs to be realized is the importance of being able to understand the condition of the community especially regarding their knowledge related to this Law and of course social workers in general. Therefore, the purpose of this study is to determine public knowledge about Law Number 14 of 2019 on social worker. The research method is quantitative with descriptive type. The sampling technique used is simple random sample, where the number of respondents reached 222 people. The results of this study indicate that the knowledge of the community belongs to the very good group with a value reaching 50.75 points accumulatively, so to be able to maintain this, a concrete step is needed to be able to maintain or even maximize the knowledge of the community, where this can be implemented through socialization programs and of course research that periodically measures the level of public knowledge about Law Number 14 of 2019 on social worker.